PENERAPAN PRIVATE ENFORCEMENT DALAM PENEGAKAN HUKUM PERSAIANGAN USAHA DI INDONESIA, AMERIKA SERIKAT DAN UNI EROPA - Muhammad Alim Kurniawan; Siti Anisah (Jurnal Penegakan Hukum Indonesia, 2021)
The study, entitled "the Application of Private Enforcement in Competition Law Enforcement in Indonesia, United State of America and European Union" raises two problem formulations, namely: how is the provision and application of private enforcement of competition law in the United States of America and European Union, and how is the provision and application of private enforcement of competition law in Indonesia? This research is a normative or doctrinal legal research, which describes, explains and analyzes legal materials that refer to the laws and regulations in Indonesia, the United States of America and European Union. Analysis of legal materials uses a qualitative descriptive approach, which is carried out by collecting legal materials, qualifying them, connecting theories related to research problems, drawing conclusions to determine the results and recommendations. The results of this study indicate that the occurrence of business competition law vacuum in Indonesia is related to the implementation of private enforcement of competition law. Thus, the authors explain the conditions and application of private enforcement of business competition law in effect in the United States of America and the European Union as well as alternatives that can be used in terms of implementing private enforcement of competition law in Indonesia based on legal principles in force in Indonesia.